Effect of In0.70Ga0.30As quantum dot insertion in the middle cell of InyGa1-yP/InxGa1-xAs/Ge triple-junction for solar cells. (January 2021) - Aissat, A.; Nacer, S.; Vilcot, J.P.
Abstract: This paper focuses on the simulation and optimization of electrical and structural properties of high efficiency InGaP/InGaAs/Ge triple junction solar cells that incorporate In0.7 Ga0.3 As quantum dots with in the GaAs middle cell material. Current density-voltage (J-V ), external quantum efficiency (EQE) and capacitance-voltage (C-V) characteristics have been simulated and discussed. Results show that 30 pairs of In0.70 Ga0.30 As (QD)/GaAs (barrier) in the middle cell provide a relative enhancement of 13% in EQE in the 900–1000 nm wavelength range. This leads to a short-circuit current of 20 mA/cm 2, an open circuit voltage of 2.3 V, a fill factor of 81.73%, and a conversion efficiency of 39.03%. The C-V revealed that a relatively high number of interfacial states are present in the 3-J cell structure including the QD layers, which decreases the open circuit voltage. In this study we benefited 18% of relative efficiency. Highlights: This paper focuses on the simulation and optimization of electrical and structural properties. InGaP/GaAs/Ge triple junction (3-J) solar cell incorporated by variable number of In0.7 Ge0.3 As. In this goal, current density-voltage, external quantum efficiency and the capacitance-voltage. This leads to a short-circuit current of 19.97 mA/cm 2, VOC  = 2.3 V, FF = 81.73%, η = 39.03%. The C-V revealed that a relatively high number can be present in the 3-J included the QD layers.